Liver Transplantation for Alcoholic Liver Disease. Issue 5 (May 2016) - Addolorato, Giovanni; Bataller, Ramón; Burra, Patrizia; DiMartini, Andrea; Graziadei, Ivo; Lucey, Michael R.; Mathurin, Philippe; O'Grady, John; Pageaux, Georges; Berenguer, Marina
Abstract : Alcohol-related liver disease is the second most frequent indication for liver transplantation (LT), yet as many as 90% to 95% of patients with alcohol-related end-stage liver disease are never formally evaluated for LT. Furthermore, despite its significance as a cause of chronic liver disease and indication for LT, it has received little attention in recent years for several reasons, including the good posttransplant short-term results, and the lack of specific "drugs" used for this disease. A writing group, endorsed by the International Liver Transplant Society, was convened to write guidelines on Liver Transplantation for Alcoholic Liver Disease to summarize current knowledge and provide answers to controversial and delicate ethical as well as clinical problems. We report here a short version of the guidelines (long version available atwww.ilts.org ) with the final recommendations graded for level of evidence. The writing group membership is expected to remain active for 5 years, reviewing the guideline annually, and updating the online version when appropriate. Abstract : The ILTS guidelines for liver transplantation for alcoholic liver disease are set forth in this publication. Considerations include the candidate population and the challenges regarding both the assessment of sobriety before and the maintenance of quality of life after transplantation. The authors identify special considerations, including immunosuppression in this setting and the special considerations regarding patients with acute alcoholic hepatitis.